MEDIA PEMBELAJARAN BERBASIS ICT TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWIRAUSAHAAN SMK - Suryati (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2016)
This research aims to analyze the effect of ICT based learning to motivation to learn and students learning outcomes in Vocational High School Kampar. The total population is all students school at Kampar. The sampling technique is purposive sampling. The type of data in this study is primary data obtained by questionaire. And secondary data is students learning outcomes obtained from entrepreneurship education teachers. Methods of data analysis using path analysis with spss program. The results of this study indicated that the ICT based learning to motivation to learn and students learning outcomes have positive and significant effects to motivation to learn and students learning outcomes in Vocational High School Kampar.